Use of ergogenic aids among Brazilian athletes: a cross-sectional study exploring competitive level, sex and sports - de Oliveira, Géssyca T.; de Souza, Hiago L. R.; Meireles, Anderson; dos Santos, Marcelo P.; Leite, Laura H. R.; Ferreira, Renato M.; Marocolo, Moacir (Frontiers in Sports and Active Living, 2023)
Was investigated ergogenic aids (EAs) used by Brazilian athletes and their association with performance, sex, sports classification, and modality. It identified the main purposes of EAs and their prescription. Methods: 239 athletes of 15 modalities, ranging from regional to international level, answered a survey online. Results: Highly competitive athletes consumed nutritional and mechanical aids more (OR=1.96 CI95% [1.28-2.9]; OR=1.79 CI95% [1.29-2.47]), while the use of psychological EAs decreased (OR= 1.66 95% CI [1.18-2.94]; p=0.001). Male athletes (OR=1.44 CI95% [1.11-2.88]) and individual sports practitioners ) used nutritional aids more. Triathlon athletes had higher nutritional EA use, while soccer athletes had lower. Combat sports athletes had higher pharmacological EA use. Conclusion: Athletes use nutritional and pharmacological aids more to improve performance and gain lean body mass. Mechanical aids were used for recovery and psychological aids for motivation. Self-prescription is common, especially for pharmacological aids.